TEACHER SOCIAL COMPETENCE IN CREATING A POSITIVE LEARNING ENVIRONMENT IN THE DIGITAL ERA - Ramadani, Suci; _, Nuzuliya; Hidayah, Arvina Nur (Jurnal Ilmu Pendidikan Ahlussunnah, 2025)
This research aims to analyze teachers’ social skills in creating a positive learning environment in the digital era. This research uses qualitative methodology through a literature review approach. The results of this research show that social competence is the ability to interact effectively, understand other people’s feelings, communicate effectively, and show empathy. A person’s ability to interact and communicate well with other people with the aim of building harmonious relationships and supporting social development within a group is known as social competence in creating a positive environment. Therefore, it is important for individuals to improve their social skills. This improvement can be achieved through a variety of means, including training, self-development, and professional experience. Individuals contribute to building a supportive and uplifting environment in the digital era